2019
DOI: 10.3390/su12010128
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Evaluation of Bread Wheat Varieties from Participatory Breeding: A Combination of Performance and Robustness

Abstract: Participatory plant breeding (PPB) is based on the decentralization of selection in farmers' fields and their involvement in decision-making at all steps of the breeding scheme. Despite the evidence of its benefits to develop population varieties adapted to diversified and local practices and conditions, such as organic farming, PPB is still not widely used. There is a need to share more broadly how the different programs have overcome scientific, practical, and organizational issues and produced a large numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Results showed that commercial varieties were less stable across farms in terms of grain yield than PPB populations, which highlights the fact that homogeneous commercial varieties are sensitive to poor conditions but valorize better fertile environments [46]. This productivity stability of PPB populations seems to be associated with greater stability in tillering capacity rather than in grain filling as indicated by the more stable grain number per m 2 .…”
Section: Spatio-temporal Stability Of Ppb Populations and Commercial mentioning
confidence: 93%
See 2 more Smart Citations
“…Results showed that commercial varieties were less stable across farms in terms of grain yield than PPB populations, which highlights the fact that homogeneous commercial varieties are sensitive to poor conditions but valorize better fertile environments [46]. This productivity stability of PPB populations seems to be associated with greater stability in tillering capacity rather than in grain filling as indicated by the more stable grain number per m 2 .…”
Section: Spatio-temporal Stability Of Ppb Populations and Commercial mentioning
confidence: 93%
“…In France, this has resulted in an increased use of variety mixtures in recent years [64] by farmers in organic as well as in conventional farming. In another approach studying stability on the same experiment [46] using dynamic indicators (Wricke's ecovalences), it was found that all PPB populations were more stable over farms than commercial lines for GY, and some of them were more stable for PC than the two commercial lines. All PPB populations were also more stable in time than the two commercial lines for PC.…”
Section: Spatio-temporal Stability Of Ppb Populations and Commercial mentioning
confidence: 99%
See 1 more Smart Citation
“…The aims of this program are (i) to study on-farm management of crop diversity [3], (ii) to develop population-varieties adapted to organic and low-inputs agriculture in the context of a participatory plant breeding program involving a collective of farmers, facilitators and researchers [4], [5] and, (iii) to co-develop methods and tools such as data management tools, experimental designs and statistical methods adapted to on-farm experiments [6,7], in order to foster genetic and social innovations. In this context, participants have (i) developed, evaluated, and measured at global and individual levels new population-varieties [6,8,9] and (ii) fostered seed and knowledge circulation among participants in a large network of farms (more than 100 farms in 2018). This program therefore produces a lot of data, and, in particular, relational information between seed lots (trace-ability) that can be represented as a network (figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The aims of this program are (i) to study on-farm management of crop diversity [3], (ii) to develop population-varieties adapted to organic and low-inputs agriculture in the context of a participatory plant breeding program involving a collective of farmers, facilitators and researchers [4], [5] and, (iii) to co-develop methods and tools like data management tools, experimental designs and statistical methods adapted to on-farm experiments [6,7], in order to foster genetic and social innovations. In this context, participants have (i) developed, evaluated, and measured at global and individual levels new population-varieties [6,8,9] and (ii) fostered seed and know-how circulation among participants in a large network of farms (more than 100 farms in 2018). This program therefore produces a lot of data, and, in particular, relational information between seed lots (trace-ability) that can be represented as a network (figure 1).…”
Section: Introductionmentioning
confidence: 99%